Upaya Peningkatan Pengetahuan tentang Penyakit Kulit Infeksi pada Masyarakat di Pantai Bungus Kecamatan Bungus Teluk Kabung Padang - Qaira Anum (Jurnal Pengabdian Warta Andalas, 2016)
Infectious skin disease consists of a skin disease caused by bacterial, fungal, viral, and parasitic infestations. Health education "Efforts to increase knowledge about infectious skin disease" refers to the people on the beach Bungus Bungus sackcloth Bay District of Padang. And treatment in 41 patients with skin disease.